The Effects of Different Ethanol Concentration on Total Phenolic and Total Flavonoid Content In Malaysian Propolis - Najihah, Yusof; Mimi Sakinah, A. M.; Kutty, R. Veloo (IOP Publishing, 2020)
As compared to honey, propolis was considered 'less explored' in active compounds characterization study. The abundance of phytochemicals in propolis contributes to various medicinal properties such as antimicrobial, anticancer, wound healing and antioxidative. The most common antioxidant groups found in propolis are phenolic acids and flavonoids. Hence, in the current study, we investigated the relationship between different ethanol concentrations on the total phenolic content (TPC) and total flavonoid content (TFC) extracted from propolis. Crude propolis was crushed and sieved before ultrasonic extractions using different ethanol concentrations (20, 50, 80%). The determination of total phenolic content was obtained from the reaction of propolis extract with Folin- Ciocalteu reagent. The result of the total phenolic content was obtained from gallic acid calibration curve and represented in gallic acid equivalent (GAE). Meanwhile, quantification of total flavonoid content was obtained from the reaction of the extract with methanolic solution of aluminum chloride (AlCl3). The result of the total flavonoid content of the propolis was acquired from quercetin calibration curve and represented in quercetin equivalent (QE). The highest TPC and TFC were recorded at 80% ethanol being 8.898 mg GAE/ml and 0.034 mg QE/ml respectively. From the experimental data, it is shown that TPC and TFC are directly propotional to ethanol concentration.